Influence of oxygen pressure and aging on LaAlO3 films grown by pulsed laser deposition on SrTiO3 substrates - Park, Jihwey (2014)
The crystal structures of LaAlO3 films grown by pulsed laser deposition on SrTiO3 substrates at oxygen pressure of 10−3 millibars or 10−5 millibars, where kinetics of ablated species hardly depend on oxygen background pressure, are compared. Our results show that the interface between LaAlO3 and SrTiO3 is sharper when the oxygen pressure is lower. Over time, the formation of various crystalline phases is observed while the crystalline thickness of the LaAlO3 layer remains unchanged. X-ray scattering as well as atomic force microscopy measurements indicate three-dimensional growth of such phases, which appear to be fed from an amorphous capping layer present in as-grown samples.